2002
DOI: 10.1152/ajplung.00363.2001
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β-induced airway hyperresponsiveness enhances substance P in intrinsic neurons of ferret airway

Abstract: Dey. Interleukin-1␤-induced airway hyperresponsiveness enhances substance P in intrinsic neurons of ferret airway. Am J Physiol Lung Cell Mol Physiol 283: L909-L917, 2002. First published April 12, 2002 10.1152/ajplung.00363.2001.-Interleukin (IL)-1␤ causes airway inflammation, enhances airway smooth muscle responsiveness, and alters neurotransmitter expression in sensory, sympathetic, and myenteric neurons. This study examines the role of intrinsic airway neurons in airway hyperresponsiveness (AHR) induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
39
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 50 publications
(86 reference statements)
3
39
0
1
Order By: Relevance
“…Irritant exposure during this developmental phase may be a predisposing factor to the pathogenic mechanisms leading to neurogenic inflammation (41). In ferret, we have shown that increased SP innervation after O 3 exposure is associated with increased airway smooth muscle responsiveness (31,42,43). In rat, SP contracts airway smooth muscle and increases vascular permeability (13,40).…”
Section: Discussionmentioning
confidence: 94%
“…Irritant exposure during this developmental phase may be a predisposing factor to the pathogenic mechanisms leading to neurogenic inflammation (41). In ferret, we have shown that increased SP innervation after O 3 exposure is associated with increased airway smooth muscle responsiveness (31,42,43). In rat, SP contracts airway smooth muscle and increases vascular permeability (13,40).…”
Section: Discussionmentioning
confidence: 94%
“…Ozone-induced airway hyperreactivity is blocked by a neurokinin receptor (NK1) antagonist in guinea pigs 3 days after ozone exposure (67) and in ferret tracheas in vitro (64), demonstrating a role for tachykinins in ozone-induced hyperractivity. IL-1b can stimulate substance P expression directly (68,69), and also indirectly via induction of nerve growth factor (70), which also increases Figure 8. Blocking IL-1 receptors prevented extracellular deposition of eosinophil major basic protein (MBP) (labeled with an antibody to MBP) within airways 3 days after ozone exposure.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Fischer and colleagues (18) showed that, 24 hours after allergen challenge, the number of SPimmunoreactive nodose ganglionic neurons in guinea pigs increased by 25%, which was mimicked by exogenous NGF (30). In ferrets, airway ozone exposure increases SP levels in the cholinergic cell bodies and in parasympathetic nerves located in tracheal smooth muscle (31), which is mimicked by the cytokine/neurokine IL-1b (11). Our results show that, in guinea pigs, neither NGF nor IL-1b changed the parasympathetic neurons to sensory-like (SP) or sympathetic (TH-or NPY-positive) phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine-like molecules (neurokines), such as IL-1b, leukemia inhibitory factor (LIF), ciliary neurotrophic factor, glial-derived neurotrophic factors, and others, may also alter nerves directly or indirectly. Although there is sufficient evidence that neurokines and NTs are increased in the blood (7), skin (8), and lungs (4, 9, 10) in inflammatory diseases, there are relatively few studies showing how that these molecules directly affect airway parasympathetic nerves (11)(12)(13).…”
mentioning
confidence: 99%